Good end-of-life care in nursing home according to the family carers' perspective: A systematic review of qualitative findings. (June 2019) - Gonella, Silvia; Basso, Ines; De Marinis, Maria Grazia; Campagna, Sara; Di Giulio, Paola
Background: Nursing homes are becoming a common site where delivering end-of-life care for older adults. They often represent the junction between the curative and the palliative phase. Aim: To identify the elements that nursing home residents' family carers perceive as good end-of-life care and develop a conceptual model of good end-of-life care according to the family perspective. Design: Systematic review (PROSPERO no. 95581) with meta-aggregation method. Data Sources: Five electronic databases were searched from inception between April and May 2018. Published qualitative studies (and mixed-method designs) of end-of-life care experience of nursing home family carers whose relative was dead or at the end-of-life were included. No language or temporal limits were applied. Results: In all, 18 studies met inclusion criteria. A 'life crisis' often resulted in a changed need of care, and the transition towards palliative care was sustained by a 'patient-centered environment'. Family carers described good end-of-life care as providing resident basic care and spiritual support; recognizing and treating symptoms; assuring continuity in care; respecting resident's end-of-life wishes; offering environmental, emotional and psychosocial support; keeping family informed; promoting family understanding; and establishing a partnership with family carers by involving and guiding them in a shared decision-making. These elements improved the quality of end-of-life of both residents and their family, thus suggesting a common ground between good end-of-life care and palliative care. Conclusion: The findings provide a family-driven framework to guide a sensitive and compassionate transition towards palliative care in nursing home.